MODEL PEMBELAJARAN DISCOVERY (DISEL): PENGEMBANGAN KARAKTER KEDISIPLINAN KURIKULUM MERDEKA BELAJAR - Elsya Sulvia Heryadi; Iis Nurasiah; Arsyi Rizqia Amalia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Character education is an encouragement referred to the students in order to become fully human with character in conscience, reason, body, taste and intention. The study described in this article is designed to improve the learning discipline of fifth-grade students by using the Discovery Learning (diesel) model. This research is a Classroom Action Research by using the Kemmis and McTaggart method which is conducted through two cycles, Cycle I and Cycle II. Participants in this study involved 29 students, 18 male and 11 female students. Data analysis used descriptive analysis and quantitative analysis. Data collection techniques used interviews, observations, and questionnaires. The results of the study indicated that the pre-cycle got an average value of 54, in the first cycle, it increased to 67, and in the second cycle, it increased to 84. Based on the results, there was a significant improvement from cycle I to cycle II of 17. It means that it could be classified as very good. In addition, it could be concluded that applying the Discovery Learning model could improve the learning discipline of elementary school students. It was recommended for schools that educators should increase creativity in providing teaching to students. It was not fixated on conventional teaching methods, but it should use varied and more innovative learning models such as the Discovery Learning model or other models. Hence, students could be more independent, creative, and disciplined.